OM-101 Decreases the Fibrotic Response Associated with Proliferative Vitreoretinopathy - Zeev Dvashi; Keren Ben-Yaakov; Tamir Weinberg; Yoel Greenwald; Ayala Pollack (Journal of Ophthalmology)
Purpose. This study aimed to investigate the effect of OM-101 on the fibrotic response occurring in proliferative vitreoretinopathy (PVR) in an animal model. Methods. Antifibrotic effect of OM-101 was investigated in vivo. As control, eight weeks old c57black mice underwent intravitreal injection with Hepes (group A) or dispase (0.3 units), to induce retinal detachment (RD) and PVR. The dispase-injected mice were randomly divided into two groups B and C (N=25 mice); in group C, the eyes were treated with intravitreal injection of OM-101 (3 μl), and group B with PBS, as a control. After additional five days, mice were injected with the same initial treatment. Three days later, mice were euthanized, and the eyes were enucleated and processed for histological analysis. Results. Intravitreal injection of dispase caused RD in 64% of the mice in group B, and 93% of those mice had PVR. Only 32% of mice treated with OM-101 and dispase (group C) developed RD, and only 25% of those developed PVR. Conclusions. OM-101 was found effective in reducing the incidence of RD and PVR maintaining the normal architecture of the retina. This study suggests that OM-101 is a potentially effective and safe drug for the treatment of PVR patients.